Modalitas Pencitraan untuk Diagnosis Myxoma Jantung - Hadiyanti (Cermin Dunia Kedokteran, 2023)
Myxoma jantung merupakan tumor jantung jinak primer yang paling umum, biasanya ada di atrium kiri dengan titik perlekatan di daerah fossa ovalis. Modalitas pencitraan untuk diagnosis myxoma jantung di antaranya ekokardiografi, computed tomography (CT), magnetic resonance imaging (MRI).   Cardiac myxoma is the most common primary benign heart tumor, usually in the left atrium with an attachment point in the fossa ovalis area. Many imaging modalities for cardiac myxoma diagnosis include echocardiography, computed tomography (CT), and magnetic resonance imaging (MRI).